Epidermal growth factor promotes intestinal secretory cell differentiation in weaning piglets via Wnt/β-catenin signalling. (25th April 2020) - Wang, L. X.; Zhu, F.; Li, J. Z.; Li, Y. L.; Ding, X. Q.; Yin, J.; Xiong, X.; Yang, H. S.
Abstract : Small intestinal epithelium homeostasis involves four principal cell types: enterocytes, goblet, enteroendocrine and Paneth cells. Epidermal growth factor (EGF ) has been shown to affect enterocyte differentiation. This study determined the effect of dietary EGF on goblet, enteroendocrine and Paneth cell differentiation in piglet small intestine and potential mechanisms. Forty-two weaned piglets were used in a 2 × 3 factorial design; the major factors were time post-weaning (days 7 and 14) and dietary treatment (0, 200 or 400 µg/kg EGF supplementation). The numbers of goblet and enteroendocrine cells were generally greater with the increase in time post-weaning. Moreover, the supplementation of 200 µg/kg EGF increased ( P < 0.01) the number of goblet and enteroendocrine cells in villus and crypt of the piglet small intestine as compared with the control. Dietary supplementation with 200 µg/kg EGF enhanced ( P < 0.05) abundances of differentiation-related genes atonal homologue 1, mucin 2 and intestinal trefoil factor 3 messenger RNA (mRNA ) as compared with the control. Piglets fed 200 or 400 µg/kg EGF diet had increased ( P < 0.05) abundances of growth factor-independent 1, SAM pointed domain containing ETS transcription factor and pancreatic and duodenal homeobox 1 mRNA, but decreased the abundance ( P < 0.01) of E74 like ETS transcription factor 3 mRNA as compared with the control. Animals receiving 400 µg/kg EGF diets had enhanced ( P < 0.05) abundances of neurogenin3 and SRY-box containing gene 9 mRNA as compared with the control. The mRNA abundance and protein expression of lysozyme, a marker of Paneth cell, were also increased ( P < 0.05) in those animals. As compared with the control, dietary supplementation with 200 µg/kg EGF increased the abundance of EGF receptor mRNA and the ratio of non-phospho(p)-β-catenin/β-catenin ( P < 0.05) in villus epithelial cells at days 7 and 14. This ratio in crypt epithelial cells was higher ( P < 0.05) on the both 200 and 400 µg/kg EGF groups during the same period. Our results demonstrated that dietary EGF stimulated goblet, enteroendocrine and Paneth cell differentiation in piglets during the post-weaning period, partly through EGFR and Wnt/β-catenin signalling.